2006
DOI: 10.1111/j.1399-3089.2005.00259.x
|View full text |Cite
|
Sign up to set email alerts
|

Rat hepatocyte engraftment in severe combined immunodeficient × beige mice using mouse‐specific anti‐fas antibody

Abstract: This novel model represents a simple and robust system of xenogeneic hepatocyte transplantation that could be applied to studies of liver biology, regeneration and hepatocyte transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…We confirmed the specie-specificity of Jo2 antibody [32] by incubating human liver cell line (HepG2) with Jo2 antibody. Jo2 antibody did not stain the human hCD95+ hepatocyte cell line (Figure S1A).…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…We confirmed the specie-specificity of Jo2 antibody [32] by incubating human liver cell line (HepG2) with Jo2 antibody. Jo2 antibody did not stain the human hCD95+ hepatocyte cell line (Figure S1A).…”
Section: Resultssupporting
confidence: 64%
“…However, these mice have disadvantages including neonatal death, poor health and, most importantly, the lack of a human immune system [19]. To overcome these deficiencies, the A2/NSG/Fas-humanized mouse model enables inducible depletion of murine hepatocytes through the Fas apoptotic signaling pathway, resulting in elevated human liver repopulation in mice transplanted with human liver progenitor and hematopoietic stem cells [32], [33], [34], [36], [51]. Additionally, the A2/NSG background permits highly efficient engraftment and development of human xenografts including human hematopoietic stem cells compared to current immunodeficient mouse models [52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wilson et al [9] studied engraftment of rat hepatocytes transplanted into livers of severe combined immunodeficient (SCID) × beige hybrid mice following induction of mouse hepatocyte apoptosis using a specific anti‐mouse agonistic Fas monoclonal antibody. They observed that mice with engraftment of rat hepatocytes of >50% were protected from Fas‐mediated liver hemorrhage and hepatocyte apoptosis, and did not show an increase in liver enzymes after administration of anti‐mouse agonistic Fas monoclonal antibody.…”
Section: Cell Transplantationmentioning
confidence: 99%